2016
DOI: 10.1080/14786419.2016.1253075
|View full text |Cite
|
Sign up to set email alerts
|

Melicodenine I, a new quinolinone alkaloid from Melicope denhamii leaves

Abstract: A new quinolinone alkaloid, Melicodenine I (1), along with five known compounds, bergapten (2), isoevodionol methyl ether (3), isoevodionol (4), ternatin (5), β-sitosteryl-3-O-β-D-glucopyranoside (6) and a mixture of β-sitosterol and stigmasterol were isolated from Melicope denhamii leaves, and their structures were elucidated using H NMR,C NMR, 2D NMR and UPLC-qToF-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Compound 2 indicated that 27 carbon signals were utterly separated in the 13 C NMR spectra, including five methyl carbons, two methylene carbons, nine methine carbons, one carbonyl carbon, and ten quaternary carbons. From the NMR ( 1 H, 13 C) NMR spectrum exhibited that the structure of 2 is a Diels-Alder adduct moiety and was confirmed by HMBC spectrum (Nakashima et al, 2012;George et al 2016). The HMBC correlation, an N-methyl at d H 3.80, and an aromatic at d (H-4)], indicating the structure of 2 are Diels-Alder adduct.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Compound 2 indicated that 27 carbon signals were utterly separated in the 13 C NMR spectra, including five methyl carbons, two methylene carbons, nine methine carbons, one carbonyl carbon, and ten quaternary carbons. From the NMR ( 1 H, 13 C) NMR spectrum exhibited that the structure of 2 is a Diels-Alder adduct moiety and was confirmed by HMBC spectrum (Nakashima et al, 2012;George et al 2016). The HMBC correlation, an N-methyl at d H 3.80, and an aromatic at d (H-4)], indicating the structure of 2 are Diels-Alder adduct.…”
Section: Resultsmentioning
confidence: 81%
“…Many alkaloids from Melicope show biological activities as cytotoxic agents (Chen et al 2003;Nakashima et al 2012), and antimalaria (Rasamison et al 2016). Recently studies on Melicope resulted in the hybrid compound by [2 þ 2] cycloaddition and a Diels-Alder adduct from incorporated phenylpropanoid-phenylpropanoid, alkaloid-alkaloid, alkaloid-benzopyran, and alkaloid-phenylpropanoid derivatives (Nakashima et al 2011(Nakashima et al , 2012George et al 2016;Saputri et al 2021). Three new compounds, melicodenine J (1) is a [2 þ 2] cycloaddition, melicodenines K (2), and L (3) are Diels-Alder adduct derivatives were isolated from M. denhamii leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Elephanthopus scaber and Mimosa pudica, there is no detailed knowledge of the chemistry of Melicope glomerata. Other species of Melicope quinoline alkaloids (the same group as quinine/chloroquine) have been identified [47,48], but with a similar cyclobutane moiety as the δ-truxinate (melicodenine D: (Figure 3c), so it is reasonable to expect related structures in Melicope glomerata. With the prevalence of resistance to quinine across the world [49] and predicted resistance development to artemisinin [38], Melicope glomerata may be a valuable research option in the search for alternatives.…”
Section: Ethnopharmacological Significancementioning
confidence: 99%
“…2-Quinolones are important synthetic scaffolds found in many natural products [1][2][3] and biologically active compounds. [4][5][6][7][8][9][10] The preparation of the 2-quinolone cores has been recognized with interest in medicinal chemistry and drug discovery.…”
Section: Introductionmentioning
confidence: 99%